Mismatch repair enzyme expression in primary and castrate resistant prostate cancer - Belinda Nghiem; Xiaotun Zhang; Hung-Ming Lam; Lawrence D. True; Ilsa Coleman; Celestia S. Higano; Peter S. Nelson; Colin C. Pritchard; Colm Morrissey (Asian Journal of Urology)
Objective: Although the utility of immunohistochemistry (IHC) for assessing mismatch repair (MMR) protein expression has been demonstrated in solid tumors including primary prostate cancer (PCa), its utility has not been assessed in castration-resistant PCa (CRPC). Methods: Tissue microarrays were constructed from 127 radical prostatectomies and 155 CRPC metastases from 50 patients. MMR (MLH1, MSH2, MSH6, and PMS2) expression was assessed by IHC and gene expression arrays. Associations between MMR protein expression in PCa and CRPC and biochemical recurrence (BCR) or time from diagnosis to death respectively were determined. Results: There was no correlation between levels of MMR protein and BCR. Absence of MSH2 and MSH6 was the most pronounced at 15% and 22% in PCa and 17.8% and 16% in CRPC patients, respectively. MSH2 and MSH6 protein were absent in 9.4% and 8% of PCa and CRPC respectively. Absence of individual MMR proteins did not correlate with BCR or time from diagnosis to death. However absent MSH2/MSH6 in CRPC was associated with shorter time to death (p = 0.0006). Loss of MSH2 was verified at the gene expression level. This finding correlated with microsatellite instability previously reported in this CRPC cohort. Conclusion: The absence of MLH1, MSH2, MSH6, and PMS2 protein and combinations thereof are frequent in PCa. Loss of MSH2/MSH6 protein may predict poor outcome in patients with CRPC. Keywords: Mismatch repair, Castration resistant prostate cancer, MLH1, MSH2, MSH6, PMS2